2016
DOI: 10.1080/09637486.2016.1195797
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of green tea catechins in a full-fat milk system under conditions mimicking the cheesemaking process

Abstract: Due to their well-known health benefits, green tea catechins have received recent attention as natural additives in foods such as dairy products. However, they may present some irreversible associations with milk components (e.g. protein and milk fat globules). To investigate the behaviour of two important green tea catechins, (+)-catechin (C) and (-)-epigallocatechin gallate (EGCG), in a standard whole milk system under the conditions of cheesemaking, 250 and 500 ppm of each catechin were added to whole milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…This was plausible that the overestimation of the total phenolic content of green tea powder itself by Folin-Ciocalteu reagent. Some studies found that the Folin-Ciocalteu reagent may overestimate the antioxidant substances from food samples (Everette et al, 2014;Rashidinejad et al, 2016b;Cutrim & Cortez, 2018). As Folin-Ciocalteu reagent was formerly used to determine tryptophan (an aromatic amino acid which is a nonphenolic group), and hence the protein content might contribute a higher phenolic content from the food samples by reducing the Folin-Ciocalteu reagent into blue-green complex (Everette et al, 2010).…”
Section: Total Phenolic Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…This was plausible that the overestimation of the total phenolic content of green tea powder itself by Folin-Ciocalteu reagent. Some studies found that the Folin-Ciocalteu reagent may overestimate the antioxidant substances from food samples (Everette et al, 2014;Rashidinejad et al, 2016b;Cutrim & Cortez, 2018). As Folin-Ciocalteu reagent was formerly used to determine tryptophan (an aromatic amino acid which is a nonphenolic group), and hence the protein content might contribute a higher phenolic content from the food samples by reducing the Folin-Ciocalteu reagent into blue-green complex (Everette et al, 2010).…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…From most of the previous studies, the decline in total antioxidant activity of milk tea was observed when the skimmed/semi-skimmed milk was added instead of whole milk (Van Het Hof et al, 1998;Langley-Evans, 2000;Lorenz et al, 2007;Ryan & Sutherland, 2011;Egert et al, 2013;Xie et al, 2013) while no significant changes (Leenen et al, 2000;Bartoszek et al, 2018), or even enhance in total antioxidant activity in tea (Mirzaei & Mirzaei, 2013) were reported when the whole milk was used. It might be because milk contains numerous fat-soluble antioxidants such as vitamin E and vitamin A (Rashidinejad et al, 2016b), and thus, skimming off the milk fat might be one of the important factors to reduce its antioxidant activity (Langley-Evans, 2000;Ryan & Petit, 2010).…”
Section: Ferric Iron Reducing Antioxidant Power (Frap)mentioning
confidence: 99%
“…Tea is a very important source of phenolic substances and it is stated that the polyphenols in tea have stronger antioxidant activity than synthetic antioxidants such as BHA, BHT and DL-alpha-tocopherol [6, more meaningful to use fresh tea shoots directly instead of green tea for a source of the polyphenols. Although, numerous researches in literature [15][16][17][18][19] were carried out on the polyphenols from different kinds of tea in particular green tea. To the best of our knowledge, there are limited studies on the polyphenols of fresh tea shoots.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that phenolic compounds synthesized as secondary metabolites in plants have many pharmacological properties such as antioxidant, antimutagenic, anticarcinogenic and antibacterial activity (Aires et al, 2016;Sanz-Puig et al, 2017) and have a positive effect on many chronic diseases such as diabetes, obesity and cardiovascular diseases (Ismail et al, 2021). Therefore, recently, many studies (Amado et al, 2014;Rashidinejad et al, 2016;Pasqualone et al, 2017) on the use of extracts from plants or their byproducts containing bioactive substances such as phenolic compounds in various foods as an alternative to artificial additives or for food enrichment have been reported.…”
Section: Introductionmentioning
confidence: 99%